2014
DOI: 10.1192/bjp.bp.113.139865
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of delirium and subsyndromal delirium in an adult acute hospital population

Abstract: Background The frequency of full syndromal and subsyndromal delirium is understudied. Aims We conducted a point prevalence study in a general hospital. Method Possible delirium identified by testing for inattention was evaluated regarding delirium status (full/subsyndromal delirium) using categorical (Confusion Assessment Method (CAM), DSM-IV) and dimensional (Delirium Rating Scale-Revised-98 (DRS-R98) scores) methods. Results In total 162 of 311 patients (52%) screened positive for inattention. Delirium was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 40 publications
4
54
0
1
Order By: Relevance
“…The investigators estimated that there was a 23% prevalence and 13% incidence of SSD, and suggested that these percentages may be larger with more specific and frequent observations of mental status (4). However, depending on the criteria for defining SSD, the incidence does vary from one study to another (13). …”
Section: Discussionmentioning
confidence: 99%
“…The investigators estimated that there was a 23% prevalence and 13% incidence of SSD, and suggested that these percentages may be larger with more specific and frequent observations of mental status (4). However, depending on the criteria for defining SSD, the incidence does vary from one study to another (13). …”
Section: Discussionmentioning
confidence: 99%
“…Besides, initiating the therapeutic intervention as early as possible by detecting the early signs of delirium is essential for preventing its aggravation. With regard to the early stage of postoperative delirium, a concept exists called “subsyndromal delirium” [28-31], which is a frequent and clinically important condition that falls on a continuum between no symptoms and full delirium. The importance of starting the prophylactic intervention during the subsyndromal stage has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…SSD could be defined by categorical elements, and is usually referred to as the presence of one or more symptoms in the Confusion Assessment Method (CAM) or the core symptoms of delirium in the Diagnostic and Statistical Manual of Mental Disorders (DSM) . It could also be defined quantitatively by an intermediate delirium score range; that is, less than full‐blown delirium, but more than no delirium on the 16‐item Revised Delirium Rating . SSD is also invariably associated with adverse outcomes including longer acute care hospital stay, higher post‐discharge mortality, and a lower cognitive and functional level at follow up than patients without delirium, but appears to have better outcomes than for those with delirium …”
Section: Introductionmentioning
confidence: 99%